2017
DOI: 10.1371/journal.ppat.1006349
|View full text |Cite
|
Sign up to set email alerts
|

Skin-resident CD4+ T cells protect against Leishmania major by recruiting and activating inflammatory monocytes

Abstract: Tissue-resident memory T cells are required for establishing protective immunity against a variety of different pathogens, although the mechanisms mediating protection by CD4+ resident memory T cells are still being defined. In this study we addressed this issue with a population of protective skin-resident, IFNγ-producing CD4+ memory T cells generated following Leishmania major infection. We previously found that resident memory T cells recruit circulating effector T cells to enhance immunity. Here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 57 publications
(75 reference statements)
5
90
0
Order By: Relevance
“…Trm cells can provide much more immediate protection, and various studies have demonstrated that they provide the most effective immune protection to the host 14, 15, 17, 30…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%
See 2 more Smart Citations
“…Trm cells can provide much more immediate protection, and various studies have demonstrated that they provide the most effective immune protection to the host 14, 15, 17, 30…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%
“…Three additional key approaches are used in mice to investigate whether Trm cells are truly resident: in vivo treatment with the S1P functional antagonist, FTY720; parabiosis in which the circulatory systems of two animals are surgically connected; and fate mapping using photoconvertible cells. Treatment with FTY720 restricts the migration of circulating cells, so a stable population of Trm cells in treated mice demonstrates that these cells are neither replenished by, nor lost to, circulating populations 15, 17, 40. However, FTY720 may also inhibit egress of cells from peripheral tissues to draining lymph nodes and/or reduce cell survival 35, 41, 42, 43.…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…175 However, during low dose re-challenge, CD4 + T RM and T RM -recruited inflammatory monocytes are sufficient to provide immediate protection without the contribution from circulating T cells. 176 …”
Section: Cd4+ Trm Cellsmentioning
confidence: 99%
“…However, whether tissue-resident or circulating memory T cells are the important subset was not investigated. In a murine model of Leishmania, the Scott group demonstrated that pathogen-specific CD4 + Trm recruit inflammatory monocytes to the site of local infection via regulation of CCR2 ligands (Glennie, Volk, & Scott, 2017). The recruitment of these inflammatory monocytes was necessary to mount an effective recall response.…”
Section: Chemokines During Memory Responses: Rapidly Orchestrating Inmentioning
confidence: 99%